Women's Shelters in Turkey: A Qualitative Study on Shortcomings of Policy Making and Implementation. (March 2013) - Diner, Cagla; Toktaş, Şule
Despite a long history of women's movements and policy-making efforts to ameliorate women's status in Turkey, the number and quality of women's shelters are far from sufficient. This article aims to reveal the shortcomings of shelter policy through the lens of those "at work" on this important social issue using a qualitative research design. Forty semistructured in-depth interviews were conducted with municipal administrative officials, state social workers, and employees of civil society organizations that run shelters. The research findings reveal that there is a lack of effective authority that has the willpower to combat violence against women, and that it is difficult to keep shelters secure in a patriarchal society away from the male gaze. Furthermore, results indicate that there has been an erosion of social services provided by the state.